Global stability of a delayed virus model with latent infection and Beddington–DeAngelis infection function. (September 2020) - Wang, Yan; Lu, Minmin; Liu, Jun
Abstract: In this paper, a virus model with latent infection, Beddington–DeAngelis infection function and three time delays is proposed, and the basic reproduction number is obtained. The global dynamics of the model is analyzed by estimating the modulus of the characteristic equation and constructing an appropriate Lyapunov function. When the basic reproduction number is less than one, the virus-free steady state is globally asymptotically stable. When the basic reproduction number is greater than one, the infected steady state is globally asymptotically stable and the virus-free steady state is unstable. Highlights: A delayed model with latent infection and Beddington–DeAngelis is formulated. Local asymptotic stability of the equilibrium of the model is studied. Global stability of the equilibrium is derived by constructing Lyapunov function.